KOORDINASI BIDANG PENANGANAN FAKIR MISKIN DENGAN TENAGA KERJA SOSIAL KECAMATAN DAN DESA DALAM PROGRAM REHABILITASI SOSIAL KELUARGA BERUMAH TIDAK LAYAK HUNI DI DINAS SOSIAL KABUPATEN CIREBON - Dwi Safitri; Moh Taufik Hidayat; Moh Sutarjo (Jurnal Ilmiah Publika, 2018)
ABSTRACT This research is motived by implentation of program Rehabilitasi Sosial Keluarga Berumah Tidak Layak Huni (RS-KBLTH) which less in accordance with the technical guidelines implementation. Sosialization of the program RS-KBTLH has not run optimally. Also not and all parties related to the RS-KBTLH program like Subdistrict and Vilage is involved in the implementation.The purpose of this study is to investigate the coordinaton divison Penanganan Fakir Miskin with TKSK and Vilage in the program RS-KBLTH in regency Cirebon. The theory used is the theory of elements coordination according to Sulistyowati that consist of the communication, integration, synchronization, and mechanism. The methode used is descpirtive qualitative method approch. Analysis techniques of data reaserch is using data description analysis cossisting of reduction data, display data, and verification data.The results showed that the coordination divison Penanganan Fakir Miskin with TKSK and Vilage in the program RS-KBLTH in regency Cirebon is not running optimaly. This is evident from the involvement of party associated with RS-KBTLH programs that have not fully become executor, there is still the executing who do not undestanding the implementation of the RS-KBTLH program. Socialitation of program RS-KBTLH has not been fully touches people. Researchhers give suggestion on this research to improve coornination and cooperation among the parties involved in the RS-KBTLH program, Dinas Sosial regency Cirebon needs to socialize directly in each village, and need for increase the executor insight.